An annotated bibliography of materials in Thailand written and/or published in the Philippines, 1973-1981 - Kittima Pongsubjaroen; Picache, Ursula G.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1982)
The purpose of this study is to annotate and provide a listing of materials on Thailand written and/or published in the Philippines from August 1973 to December 1981, particularly in view of the significant researches and studies in various subject areas.
This annotated bibliography involves classified and unclassified works: theses (undergraduate and graduate), dissertations, special problems, seminar and conference papers, investigation papers, articles in periodicals, and miscellaneous publications on Thailand which are published and produced in the Philippines and written by Thais, Filipinos, or other nationals in the Philippines.
It is divided into two sections. Section One is the listing of theses, dissertations, special problems, and investigation papers. Section Two is the listing of seminar and conference papers, discussion papers, periodical articles, and miscellaneous publications. Both sections are classified under broad subject areas. In some cases, the broad subjects are divided further into small topics. Under each subject, entries are arranged alphabetically by author, with complete bibliographic data. Each entry is provided with an item number. The item number is referred to in the title and author indexes which are provided to facilitate the location of specific items. The entries for Thai authors in this bibliography are under their first names followed by the surnames.
A historical background of the relations between the Philippines and Thailand is given for a better understanding of this bibliography in Chapter II.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman